Beloved Enemy - Clarke, Alan; Cossey, Elmer; MacCann, Barry; Crowden, Graham; Doyle, Tony; Quitak, Oscar (Alan Clarke at the BBC, Volume 2: Disruption, 2016)
A cool hard study of "the art of the deal" on a global scale. Sir Peter, the chillingly affable chief exec of big British multi-national UKM, learns that the Soviet Union’s chief scientists are in London with government credit to spend. He's keen to flog them a tyre-production plant, based in the Ukraine, which will unshackle UKM from bothersome unions at home. But at the negotiating table, it fast becomes apparent that the Soviets are more interested in the laser technology UKM employs to vulcanise their tyres; and Peter starts to foresee a new future in military aerospace for his ever flexible firm. [letterboxd.com]